RATIONALE FOR MATHEMATICAL SOLUTION MODEL OF LABOUR SAFETY RISKS ASSESSMENT PROBLEM AT ENGINEERING ENTERPRISES - Alexander Alexandrovich Martynenko; Valery Vladimirovich Novikov (Advanced Engineering Research, 2012)
Some issues on the mathematical model justification and the solution to the problem of the labour safety risks assessment at the machine building enterprises are considered. As a result, the phases of occupational hazards threat, and the conditions which may result in workers death, injury, or disease, are discovered. Risk ranking in subdivisions and time may well in advance permit to localize subdivisions (departments) and hazards, to provide a preventive planning aimed at the workers death, injury, or disease risk reduction at the engineering enterprises.